NAKED RAKU RESEARCHES (Revista NUPEART, 2018)
Raku has been one of the favourite firing techniques since it allows low-firing and offers a wide range of colour options on glaze. Ceramicists’ researches in an effort to create different and alluring surfaces on a ceramic body have led to the enrichment of this technique with some variations. As a result of this quest, ceramic artists began experimenting with decorative effects on a ceramic body without using glaze in 1980s. Raku firing technique without using glaze, called Naked Raku in foreign sources, has twobasictypes, one-step nakedrakuandtwo-step nakedraku. Inone step nakedrakutechnique a thick slip is appliedtobisquefiredceramicpiecesand it is firedwhile it is wetandthenreduced. In two step nake drakuthin/ thick slip is applied and covered withlow- fire glazeandreduced. The aim of this study is to examine the development process of naked raku and giving examples from artist’s own experiences. The study includes today’s raku production process, the characteristics of clay, slip and glaze used in this process, and the firing technique.